The Effect of Shape and Arrangement of End Sill Stepped Cascade Weirs on Water Quality - Gubashi, Karim Rashid; Hussain, Batool Ali (Al-Nahrain Journal for Engineering Sciences, 2018)
Hydraulic structures can be accepted as the key components in improving aeration efficiency because of the strong turbulent mixing associated with substantial air bubble entrainment at these structures. Different hydraulic structures have been designed to enhance aeration such as stepped cascades. A laboratory model of stepped cascade weir with five different shapes of end sill (normal, triangle, rectangle1, rectangle2 and rectangle3) have been installed at Al- Mustansiriya University, College of Engineering to evaluate treatment system and reduced pollutants in marginal water for different flow rates (35,60 and 80 L/min). Results indicate that high removal efficiency of all pollutants parameter (Cu, Cr, Mo, Br, Fe, Mn, Zn, PO4, Cl-, ClO2, Hardness as CaCO3, NH3, NO2, Toxic matter) is for rectangle1 shape at Q=60L/min. High aeration efficiency is 45.7% for rectangle1 shape at Q=80L/min. High removal efficiency for BOD5 and COD are 48% and 47% respectively for rectangle 1 at Q=80 L/min.